Effect of Laser Therapy on Inflammation in Pneumonia or Pneumonia Sepsis through the Nf-Kb Regulatory Pathway: A Literature Review Study - Rahmad, Rahmad; Djaharuddin, Irawati; Fauzi, Yanuar Rahmat; Purbasari, Bethasiwi; Hakimah, Annisatul; Waluyo, Yose (Writing Center IMERI FMUI, 2024)
Pneumonia is the most frequent cause of death from infectious diseases is the eighth leading cause of death in the United States. Meanwhile, sepsis and septic shock remain the leading causes of death among critical patients despite decades of significant advances in supportive therapy. A major factor leading to high morbidity and mortality from septic shock is the lack of effective treatment. Many different options have been proposed, among which the prospect of low-level laser therapy is being discussed quite actively. Laser therapy is a viable way to treat pneumonia or sepsis pneumonia. It is known for its benefits as an anti-inflammatory effect that can reduce the levels of pro-inflammatory cytokines, namely IL-6, as well as increase TNFα levels and enhance the balance of inflammatory processes. Additional research is required to confirm the effect of laser therapy on inflammation, especially the NF-kB pathway in cases of pneumonia or sepsis pneumonia in vitro, in vivo and in clinical studies.